An Overview of Social Support from Spouses for Women Who Married Early in Langkaplancar District, Pangandaran Regency - Dian Novita; Siti Yuyun Rahayu Fitri; Taty Hernawaty (STIKes Budi Luhur Cimahi, 2026)
Support from a spouse, encompassing attention, encouragement, emotional care, and practical assistance, plays a vital role in sustaining wives’ psychological well-being, particularly in early marriage when readiness and adaptive capacities are still developing. This study aimed to describe how women in early marriages perceive social support received from their partners. A quantitative descriptive design was employed. The population consisted of women who married early, with 46 participants selected using a total population sampling technique. Data were collected using the Support in Intimate Relationships Rating Scale-Revised (SIRRS-R) instrument and analyzed using univariate analysis, categorizing results into high, medium, and low levels. The findings revealed that most respondents reported a moderate level of overall partner support. Across the four dimensions of support, scores were predominantly in the moderate range, with the lowest proportion observed in the esteem/emotional support dimension. Although women in early marriages receive partner support, it remains suboptimal for addressing the psychological and adaptive challenges associated with early marriage. This study highlights the need to strengthen spousal support, particularly emotional and esteem-related aspects, to enhance psychological well-being and facilitate role adjustment in early marital contexts.